Online retail in India: a comparative analysis of top business players. (3rd June 2020) - Ayodeji, Ogunmola Gabriel; Kumar, Vikas; Kumar, Surender
The robust online start-up culture has led to the rise and growth of numerous online retailers in India. However, only few of them are dominating the market, while others are still struggling start-ups. So, the business strategy becomes very much important to sustain in the fast growing market. Present work carries out a comparative analysis of the top five online retailers in India and the retailers are ranked on the basis of traffic volume. Business models of these companies have been compared along with the funding and investment strategies. Acquisitions and collaborations by these companies have also been explored to identify their market share strategy. This work presents a very comprehensive picture of the Indian online retail market, covering all major aspects.